1972
DOI: 10.1084/jem.135.2.323
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenesis of Chronic Inflammation in Experimental Antigen-Induced Arthritis

Abstract: In an experimental arthritis induced by injection of bovine serum albumin or egg albumin into the joints of previously immunized animals, it has been demonstrated that the major portion of the radioactively labeled antigens injected was localized to avascular collagenous tissues in the joint, i.e., articular cartilage, menisci, and intra-articular ligaments. The antigens were partially eluted from the tissues with 5 M guanidine solution, but not with acid buffers or by 3 M magnesium chloride. The radioactive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1
1

Year Published

1972
1972
1989
1989

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 159 publications
(45 citation statements)
references
References 14 publications
2
41
1
1
Order By: Relevance
“…The superficial distribution of large aggregates and the deep distribution of small suggested that penetration of the matrix occurred in relationship to size; this finding also supports the deposition of Ag as a formed complex. The specific staining of the aggregates for rabbit IgG, but lack of free staining for IgG in the matrix or joint space, suggests an initial local state of antigen excess without free antibody in either the tissue matrix or joint space (10). The aggregated form of Fn and its intense and highly specific staining for antibody add strong support to previous data for antigen locaiization in ACT as an immune complex (2.3,10,14,15).…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…The superficial distribution of large aggregates and the deep distribution of small suggested that penetration of the matrix occurred in relationship to size; this finding also supports the deposition of Ag as a formed complex. The specific staining of the aggregates for rabbit IgG, but lack of free staining for IgG in the matrix or joint space, suggests an initial local state of antigen excess without free antibody in either the tissue matrix or joint space (10). The aggregated form of Fn and its intense and highly specific staining for antibody add strong support to previous data for antigen locaiization in ACT as an immune complex (2.3,10,14,15).…”
Section: Discussionsupporting
confidence: 77%
“…The deposition of complexed Fn in almost normal appearing matrix surfaces continued up to 3 hours; a dramatic change occurring at 6 hours was associated with massive PMN cell interaction. This coincided with an intense Arthus reaction and in the continuing presence of immune complexes at a phase of Ag excess (10). At the Arthus peak, after 24 hours, severe damage has occurred with the surfaces stripped of their tangential layers, Fn, and cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations